Evaluasi dan Rancangan Sistem Ventilasi pada Lubang Tambang CBP-03 PT.Cahaya Bumi Perdana,Kota Sawahlunto - olivia julianti; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Cahaya Bumi Perdana uses only one ventilation system, namely the blow ventilation system which aims to provide and flow fresh air into the mine for workers' breathing and other processes that require air. Based on the initial inspection of the ventilation system used in the CBP-03 hole using only the blow ventilation system, the researchers also found duct leaks at 3 points, which resulted in loss of air circulation. This causes the quality and quantity of air to decrease, as well as the effective temperature and relative humidity to increase beyond the threshold. In June there was an explosion and the location of the mine hole where the explosion had occurred is currently close to the location of the mine progress plan following the direction of the spread of coal which has potential hazards methane gas. From the results of the air quality evaluation, it can be concluded that the effective temperature and relative humidity in canopy 2, the branches and front work have exceeded the threshold value regulated by Kepmen No.1827 K / 30 / MEM / 2018, namely the effective temperature ranges between 18-24 ° C with a maximum relative humidity of 85%. From the evaluation results, the quantity of air in and out is the same, amounting to 6.06 m3 / sec, From the results of the need for air on the front of work, the need for air for breathing 3 workers per shift is 0, 10 m3 / sec. Air requirement needed to dilute methane gas is 0.24 m3 / sec. The overall air requirement for the equipment in the CBP-03 mine hole is for 1 unit jack hammer = 1300 watts = 1.743 HP = 1.743 x 3 m3 / minute = 0.08715 m3 / sec. From the results of the design of the ventilation system using autocad 2007 the total quantity of air intake is the air entering the tunnel canopy 1 maintained at 6.06 m3 / sec plus the quantity of air throughout the front duct from the available equipment with a total quantity of 3.03 m3 / second. So the total amount of intake air from the design after the addition of the fan is 9.09 m3 / sec. Meanwhile, the need for air for workers and mining supporting equipment is 0.73 m3 / sec. The need for safe and effective maintenance of ventilation equipment and providing backup ventilation equipment and the availability of a backup power source. If one day the equipment breaks down, a replacement will be available during an emergency, so it doesn't stop air circulation in the mine pit. Keywords: Ventilation System, Evaluation, Air Requirement, Autocad 2007